Intestinal Barrier Function and Immune Homeostasis Are Missing Links in Obesity and Type 2 Diabetes Development - Riedel, Sylvia; Pheiffer, Carmen; Johnson, Rabia; Louw, Johan; Muller, Christo J. F. (Frontiers in Endocrinology, 2022)
Noncommunicable diseases, such as type 2 diabetes (T2D), place a burden on healthcare systems worldwide. The rising prevalence of obesity, a major risk factor for T2D, is mainly attributed to the adoption of Westernised diets and lifestyle, which cause metabolic dysfunction and insulin resistance. Moreover, diet may also induce changes in the microbiota composition, thereby affecting intestinal immunity. The critical role of intestinal immunity and intestinal barrier function in the development of T2D is increasingly acknowledged, however, limited studies have investigated the link between intestinal function and metabolic disease. In this review, studies reporting specific roles of the intestinal immune system and intestinal epithelial cells (IECs) in metabolic disease are highlighted. Innate chemokine signalling, eosinophils, immunoglobulin A (IgA), T helper (Th) 17 cells and their cytokines were associated with obesity and/or dysregulated glucose homeostasis. Intestinal epithelial cells (IECs) emerged as critical modulators of obesity and glucose homeostasis through their effect on lipopolysaccharide (LPS) signalling and decontamination. Furthermore, IECs create a link between microbial metabolites and whole-body metabolic function. Future in depth studies of the intestinal immune system and IECs may provide a new opportunities and targets to develop treatments and prevention strategies for obesity and T2D.